A framework for assessing robustness of water networks and computational evaluation of resilience. - Al-Almeri, Shehab Ahmed (Cranfield University, 2016)
Arid regions tend to take careful measures to ensure water supplies are secured to consumers, to help provide the basis for further development. Water distribution network is the most expensive part of the water supply infrastructure and it must maintain performance during unexpected incidents. Many aspects of performance have previously been discussed separately, including reliability, vulnerability, flexibility and resilience. This study aimed to develop a framework to bring together these aspects as found in the literature and industry practice, and bridge the gap between them. Semi-structured interviews with water industry experts were used to examine the presence and understanding of robustness factors. Thematic analysis was applied to investigate these and inform a conceptual framework including the component and topological levels. Robustness was described by incorporating network reliability and resiliency. The research focused on resiliency as a network-level concept derived from flexibility and vulnerability. To utilise this new framework, the study explored graph theory to formulate metrics for flexibility and vulnerability that combine network topology and hydraulics. The flexibility metric combines hydraulic edge betweenness centrality, representing hydraulic connectivity, and hydraulic edge load, measuring utilised capacity. Vulnerability captures the impact of failures on the ability of the network to supply consumers, and their sensitivity to disruptions, by utilising node characteristics, such as demand, population and alternative supplies. These measures together cover both edge (pipe) centric and node (demand) centric perspectives. The resiliency assessment was applied to several literature benchmark networks prior to using a real case network. The results show the benefits of combining hydraulics with topology in robustness analysis. The assessment helps to identify components or sections of importance for future expansion plans or maintenance purposes. The study provides a novel viewpoint overarching the gap between literature and practice, incorporating different critical factors for robust performance.
Keywords: water; networks; robustness; resiliency; reliability; flexibility; vulnerability; connectivity; topology; graph theory; hydraulic load; hydraulic distance